Global phosphoproteome analysis reveals significant differences between sporulated oocysts of virulent and avirulent strains of Toxoplasma gondii. (December 2021) - Wang, Ze-Xiang; Hu, Rui-Si; Zhu, Xing-Quan; Sun, Xiao-Lin; Elsheikha, Hany M.
Abstract: In this study, the differences in the phosphoproteomic landscape of sporulated oocysts between virulent and avirulent strains of Toxoplasma gondii were examined using a global phosphoproteomics approach. Phosphopeptides from sporulated oocysts of the virulent PYS strain (Chinese ToxoDB#9) and the avirulent PRU strain (type II) were enriched by titanium dioxide (TiO2 ) affinity chromatography and quantified using IBT approach. A total of 10, 645 unique phosphopeptides, 8181 nonredundant phosphorylation sites and 2792 phosphoproteins were identified. We also detected 4129 differentially expressed phosphopeptides (DEPs) between sporulated oocysts of PYS strain and PRU strain (|log1.5 fold change| > 1 and p < 0.05), including 2485 upregulated and 1644 downregulated phosphopeptides. Motif analysis identified 24 motifs from the upregulated phosphorylated peptides including 22 serine motifs and two threonine motifs (TPE and TP), and 15 motifs from the downregulated phosphorylated peptides including 12 serine motifs and three threonine motifs (TP, RxxT and KxxT) in PYS strain when comparing PYS strain to PRU strain. Several kinases were consistent with motifs of overrepresented phosphopeptides, such as PKA, PKG, CKII, IKK, MAPK, EGFR, INSR, Jak, Syk, Src, Ab1. GO enrichment, KEGG pathway analysis and STRING analysis revealed DEPs significantly enriched in many biological processes and pathways. Kinase related network analysis showed that AGC kinase was the most connected kinase peptide. Our findings reveal significant difference in phosphopeptide profiles of sporulated oocysts between virulent and avirulent T. gondii strains, providing new resources for further elucidation of the mechanisms underpinning the virulence of T. gondii . Graphical abstract: Image 1 Highlights: Phosphoproteomes of sporulated oocysts of Toxoplasma gondii virulent PYS strain (Chinese ToxoDB#9) and avirulent PRU strain (type II) were compared. 4129 differentially abundant phosphopeptides were detected. 24 and 15 abundant motifs were identified from phosphorylated peptides of PRU strain and PYS strain, respectively. Several kinases were consistent with motifs of overrepresented phosphopeptides, including PKA, PKG, CKII, IKK, MAPK, EGFR, INSR, Jak, Syk, Src, Ab1. T. gondii AGC kinase was the most connected kinase peptide.